Emergency Response Measures for Anesthesia Nursing During the COVID-19 Pandemic: West China Hospital Experiences - Zheng, Ping; Zhou, Ruihao; Yin, Lu; Yin, Xiaorong; Mao, Yongqiao; Wang, Heng; Ye, Ling; Zhu, Tao (Frontiers in Medicine, 2020)
Under the COVID-19 pandemic, how to ensure the gradual recovery of anesthesia nursing unit and avoid cross infection between surgical patients and staff is a difficult problem for hospital managers. We outlined the emergency response measures and the transition to normal operation for the anesthesia nursing unit in West China Hospital, which is a large teaching hospital. It mainly included hospital and operating room channel management, three-level screening management of patients and medical staff, classification management of patients undergoing anesthesia, recovery, training management of medical personnel, strict environmental management, and online teaching management.